2021
DOI: 10.3390/ijerph18136793
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, SARS-CoV-2 and Causal Associations in Transversal Studies: The Time-Series Analysis to Reveal Potential Confounders. Comment on Gaudio et al. Vitamin D Levels Are Reduced at the Time of Hospital Admission in Sicilian SARS-CoV-2-Positive Patients. Int. J. Environ. Res. Public Health 2021, 18, 3491

Abstract: We read with great interest the paper by Gaudio and colleagues on vitamin D and on the state of patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the time of admission [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…We read the comment by Ialongo et al [1] on our recent article with great interest [2]. We fully agree with our colleagues on the limits that a cross-sectional and transversal study approach can have in analyzing a complex phenomenon that evidently also has its own specific temporal evolution, and all of this was clearly reported in the limitations section of our study [2].…”
supporting
confidence: 72%
See 1 more Smart Citation
“…We read the comment by Ialongo et al [1] on our recent article with great interest [2]. We fully agree with our colleagues on the limits that a cross-sectional and transversal study approach can have in analyzing a complex phenomenon that evidently also has its own specific temporal evolution, and all of this was clearly reported in the limitations section of our study [2].…”
supporting
confidence: 72%
“…A further element that should be highlighted is that the approach to diagnosing COVID-19 disease has changed over the months, as Ialongo et al [ 1 ] have reported, because the availability of swabs and our ability to process them changed radically during last summer. This has brought to light cases that were previously not diagnosed, because only clearly symptomatic patients were tested in the previous months.…”
mentioning
confidence: 99%